ANALYZING INTERNAL STUDENT’S OBSTACLES IN WRITING RESEARCH PAPER AT THE FINAL GARADUATED SARJANA DGREE OF ENGLISH EDUCATION STUDY PROGRAM OF IKIP SILIWANG - Suhud Aryana; Fathan Fadilah; Wikanengsih Wikanengsih (JLER (Journal of Language Education Research), 2019)
This research is based on the importance of writing scientific papers for students. Especially the final graduated sarjana dgree students who are compiling research paper. Therefore, this reserach focuses on analyzing case studies of student’s internal problems. The aim of this reserach is to find out how much student’s internal problems in writing a research paper. This research is a case study which is part of qualitative research. Therefore, the method of this research used cuse study method. The subject of this research was a student’s final graduated sarjana dgree of English Education Study Program of IKIP Siliwangi. The instruments used were observation, questionnaire and interview. In short, the results of the research as follows; First, student felt difficult when pouring out the main ideas in writing process. Second, student felt stress when he do not know the system of writing. Third, student felt lazy with writing activities cause he can not to think critically. Fourth, student has  not experienced of writing researh paper  before. Fifth, student lack of reading books. Sixth, students luck of self motivation then appear do not confident in writing research paper. Seventh lacks understanding of the topics discussed. The last, student’s disciplines in managing time.